A cross-sectional analysis of pharmaceutical industry-funded events for health professionals in Australia. Issue 6 (30th June 2017) - Fabbri, Alice; Grundy, Quinn; Mintzes, Barbara; Swandari, Swestika; Moynihan, Ray; Walkom, Emily; Bero, Lisa A
Abstract : Objectives: To analyse patterns and characteristics of pharmaceutical industry sponsorship of events for Australian health professionals and to understand the implications of recent changes in transparency provisions that no longer require reporting of payments for food and beverages. Design: Cross-sectional analysis. Participants and setting: 301 publicly available company transparency reports downloaded from the website of Medicines Australia, the pharmaceutical industry trade association, covering the period from October 2011 to September 2015. Results: Forty-two companies sponsored 116 845 events for health professionals, on average 608 per week with 30 attendees per event. Events typically included a broad range of health professionals: 82.0% included medical doctors, including specialists and primary care doctors, and 38.3% trainees. Oncology, surgery and endocrinology were the most frequent clinical areas of focus. Most events (64.2%) were held in a clinical setting. The median cost per event was $A263 (IQR $A153–1195) and over 90% included food and beverages. Conclusions: Over this 4-year period, industry-sponsored events were widespread and pharmaceutical companies maintained a high frequency of contact with health professionals. Most events were held in clinical settings, suggesting a pervasive commercial presence in everyday clinical practice. Food and beverages, known to be associated with changes to prescribing practice, were almost always provided. New Australian transparency provisions explicitly exclude meals from the reporting requirements; thus, a large proportion of potentially influential payments from pharmaceutical companies to health professionals will disappear from public view.